OP0203 Impact of adalimumab serum concentration on efficacy and association between ANTI-DRUG antibodies and serum concentration: 24 week results from a phase III study comparing SB5 (an adalimumab biosimilar) with reference adalimumab in patients with rheumatoid arthritis. (15th June 2017) - Kay, J; Weinblatt, M; Keystone, E; Genovese, M; Ghil, J; Cheong, SY; Hong, EE
Abstract : Background: SB5 has been developed as a biosimilar of reference adalimumab (ADL). The 24-week efficacy and safety results comparing SB5 and ADL were reported previously. 1 Here we report results of subgroup analyses of efficacy by adalimumab serum trough concentration (Ctrough ) and association between anti-drug antibodies (ADA) and Ctrough . Objectives: To investigate the impact of Ctrough on efficacy and the association between ADA and Ctrough in patients with rheumatoid arthritis (RA) treated with SB5 or ADL. Methods: Patients with moderate to severe RA despite methotrexate treatment were randomly assigned to receive 40 mg of either SB5 or ADL administered subcutaneously every other week up to week 24. Blood samples were taken prior to study drug administration at weeks 0, 4, 8, 12, 16, and 24 to measure Ctrough . The optimal Ctrough cut-off point of adalimumab for good EULAR response at week 24 is reported to be 1.274 μg/mL. 2 Efficacy and immunogenicity were analysed in patients with Ctrough <1.274 μg/mL and ≥1.274 μg/mL. Results: Ctrough was measured in 178 patients each from SB5 and ADL group. The post-dose mean Ctrough was comparable up to week 24 for SB5 (range: 3.850 to 6.761 μg/mL) and ADL (range: 3.892 to 6.773 μg/mL). Generally, efficacy was higher in patients with Ctrough ≥1.274 μg/mL for both SB5 and ADL but it was comparable between SB5 and ADL regardless of Ctrough level. At week 24, the proportion of patients achieving good EULAR response, remission or low disease activity based on DAS28 was higher in patients with Ctrough ≥1.274 μg/mL than in those with Ctrough <1.274 μg/mL for both treatment groups (Figure). Other efficacy parameters, including ACR responses, DAS28, simplified disease activity index, and clinical disease activity index, showed similar results. Ctrough was higher for patients without detectable ADA, compared to those with ADA. Among patients with ADA, the proportion of patients with Ctrough ≥1.274 μg/mL was 58.0% (29/50) for SB5 and 52.1% (25/48) for ADL. Among patients without detectable ADA, the proportion of patients with Ctrough ≥1.274 μg/mL was 100.0% (121/121) for SB5 and 97.4% (114/117) for ADL. Conclusions: The presence of ADA reduces Ctrough for both SB5 and ADL. In both treatment groups, almost all patients without detectable ADA, but only slightly more than half of patients with ADA, had Ctrough ≥1.274 μg/mL at week 24. Efficacy and ADA incidence were generally comparable between SB5 and ADL regardless of Ctrough level. However, patients with Ctrough ≥1.274 μg/mL generally experienced greater efficacy of both SB5 and ADL than that in patients with Ctrough <1.274 μg/mL. References: Weinblatt ME et al. Arthritis Rheumatol. 2015; 67 (suppl 10), 8L. Chen DY et al., Ann Rheum Dis. 2015; Mar;74(3):e16. Disclosure of Interest: J. Kay Grant/research support from: Abbvie, Ardea Biosciences, Eli Lilly, Pfizer, Genentech, Roche, UCB, Consultant for: Alexion, Amgen, AbbVie, AstraZeneca, BI, BMS, Crescendo Bioscience, Eli Lilly, Epirus, Genentech, GSK, Hospira, Janssen, MSD, Novartis, Pfizer, Samsung Bioepis, Sandoz, Roche, UCB, M. Weinblatt Consultant for: Abbvie, Amgen, Samsung Bioepis, E. Keystone Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Janssen, Lilly, Novartis, Pfizer, Consultant for: Abbott, AstraZeneca, Biotest, BMS, Genentech, Janssen, Lilly, Merck, Pfizer, Samsung Bioepis, Speakers bureau: Abbott, AstraZeneca, BMS Canada, Janssen, M. Genovese Grant/research support from: Abbvie, Consultant for: Abbvie, Amgen, FkB, BI, Merck, Samsung Bioepis, J. Ghil Employee of: Samsung Bioepis Co., Ltd., S. Y. Cheong Employee of: Samsung Bioepis Co., Ltd., E. Hong Employee of: Samsung Bioepis Co., Ltd.